Managing in Tough Times: Downsized — Job Loss and Retirement Plans - Brandon Butcher; Michael S. Gutter; Brent Litchfield (EDIS)
FCS7240, a 5-page fact sheet by Brandon Butcher, Michael S. Gutter, and Brent Litchfield, answers some common questions individuals may have about what happens to retirement plans when the employee leaves a job. Includes references. Published by the UF Department of Family Youth and Community Sciences, October 2009.